+0  
 
0
63
1
avatar
The expression $6y^2-y-51$ can be rewritten as $(3Ay+B)(y-C)$, where $A$, $B$, and $C$ are positive integers. Find $(AC)^2-B$.
 Jul 10, 2020
 #1
avatar+21953 
0

6y2 - y - 51  =  (3Ay + B)(y - C)

 

Multiplying out:  (3Ay + B)(y - C)  =  3Ay2 + By - 3ACy - BC  =  3Ay2​ + (B - 3AC)y - BC

 

Since  6y2 - y - 51  =  3Ay2​ + (B - 3AC)y - BC

 

The y2-terms must be equal:  6y2  =  3Ay2​   --->   6  =  3A   --->   A  =  2

 

The y-terms must be equal:  -y  =  (B - 3AC)y   --->   -1  =  B - 3AC

     --->   since  A  =  2   --->   -1  =  B - 3(2)C   --->   -1  =  B - 6C

 

The constants must be equal:  -51  =  -BC   ---   BC  =  51

Since we are dealing only with positive integers:  B = 1     and   C = 51

                                                                        or   B =  51  and   C = 1

                                                                        or   B = 3     and   C = 17

                                                                        or   B = 17   and   C = 3

 

To get  B - 6C  =  -1  we can choose B to be 17 and C to be 3   --->   17 - 6(3)  =  17 - 18  =  -1

 

So:  A = 2   and   B = 17   and   C = 3

 

I'll let you finish the problem ...

 Jul 10, 2020

39 Online Users

avatar
avatar
avatar